Structure and flexural strength of the hot-pressed AlMgB14 ceramic - Tkachev, Dmitriy; Nikitin, Pavel Yu; Zhukov, Ilya A.; Vorozhtsov, Alexander B.; Marchenko, Ekaterina S.; Verkhoshanskiy, Yanis; Belchikov, Ivan A. (Physica scripta)
AlMgB14 materials were obtained by hot-pressing of the prereacted AlMgB14 powder. The phase composition, structure, hardness and flexural strength have been studied. The XRD studies shown that the phase composition of the obtained materials contains from 9 to 12 wt. % of the spinel MgAl2O4 phase except target AlMgB14-phase. The spinel content increases linearly with an increase in the hot-pressing temperature from 1400 °C to 1600 °C. It was found that the density of the studied materials non-linearly depends on the hot-pressing temperature. An increase in the hot-pressing temperature from 1400 °C to 1500 °C leads to an increase in the relative density of the samples from 84% to 93%, respectively. A further increase in the hot-pressing temperature to 1600 °C leads to a decrease in the relative density to 81% due to the complication of the densification processes with an increase in the spinel content. An increase in the relative density from 81% to 93% leads to an increase in the flexural strength from 121 to 314 MPa and an increase in the Vickers microhardness from 5.1 to 7.9 GPa, respectively.